Comparative Analysis of Productivity and Efficiency of Recirculating Aquaculture System (RAS) and Biofloc in Nile Tilapia (Oreochromis niloticus) Culture - Ayi Yustiati; Rany Marlianti Karimah (Fakultas Perikanan dan Kelautan Universitas Riau, 2026)
Nile tilapia (Oreochromis niloticus) culture faces challenges in achieving optimal production efficiency due to limited land availability and water resources. This study aimed to analyze and compare the productivity and efficiency of the Recirculating Aquaculture System (RAS) and Biofloc systems in Nile tilapia culture. The research employed a comparative experimental approach, measuring growth performance, Food Conversion Ratio (FCR), Survival Rate (SR), and water-quality management efficiency in both systems. The results showed that both systems significantly improved aquaculture productivity compared to conventional methods. The RAS system produced a higher daily growth rate, with productivity reaching 35 to 40 kg/m³ per cycle, survival rates of 85 to 92%, and more stable water quality. Meanwhile, the biofloc system demonstrated better feed efficiency, with an FCR ranging from 0.9 to 1.2, compared to RAS, which ranged from 1.2 to 1.5, and productivity reached 30 to 38 kg/m³ when biofloc was used as an additional nutrient source. Economically, the biofloc system was more efficient in feed and water utilization, whereas RAS was superior in environmental control and in managing high stocking density. These findings provide a scientific basis for aquaculture practitioners in determining the most suitable technology based on business scale, capital capacity, and aquaculture sustainability goals.